Metabolic age based on the BBMRI-NL 1H-NMR metabolomics repository as biomarker of age-related disease - van den Akker, EB; Trompet, S; Barkey Wolf, JJH; Beekman, M; Suchiman, HED; Deelen, J; Asselbergs, FW; Boersma, E; Cats, D; Elders, PM; Geleijnse, JM; Ikram, MA; et al. (American Heart Association, 2020)
BACKGROUND: The blood metabolome incorporates cues from the environment and the host's genetic background, potentially offering a holistic view of an individual's health status.